Evaluation of aroma in Malaysian rice landraces through sensory test and molecular approach - A.R. Site, Noorzuraini; N, Rosimah; Faridah, Q.Z.; H.N., Khairun; A.R., Mohd Shahril Firdaus; O., Mohd Ramzan (Pakistan Agricultural Scientists Forum, 2024)
Aroma is one of the primary rice grain quality traits that play a vital role in consumer preferences. In Malaysia, consumers have shown a marked preference for high-quality rice. Therefore, it is essential to identify rice landraces with considerable aroma for promotion as potential donors for the development of high-quality rice in future breeding programs to meet consumer demand and reduce dependency on imported high-quality rice types. Thirty-three rice genotypes comprising thirty Malaysian rice landraces and three modern rice cultivars were evaluated for aroma using sensory tests and molecular markers. The presence of aroma in cooked rice was determined through nose sensory evaluation by five panellists. Molecular analysis was performed using two aroma-specific SSR primers i.e., FMbadh2-E7 and Badex7-5. The sensory test revealed that only five rice landraces had a strong aroma; whereas eleven had a slight aroma. FMbadh2-E7 was found to have most of the alleles with a major allele frequency of 0.53. Whereas, Badex7-5, has a major allele frequency of 0.51, with five alleles at the locus. The dendrogram was generated by UPGMA cluster analysis using two aroma-specific primers, which characterized the rice genotypes into two distinct clusters; Cluster 1 consisted of fifteen rice landraces with non-aroma standards, while Cluster 2 consisted of fifteen rice landraces with aroma standards. Based on the sensory test and molecular approach, the identified rice landraces with aroma were i.e., Kenawit, Gertok, Pandan, Nangka, Tiga Bulan, Lumpur, Grik, Sanguo Pandan, Kurau, Bidor, and Wangi, which can be further promoted as potential donors through breeding. © 2024, Pakistan Agricultural Scientists Forum. All rights reserved.